Gasping for air: measuring patient education and activation skillsets in two clinical assessment contexts. (27th November 2020) - Wilhite, Jeffrey A; Fisher, Harriet; Altshuler, Lisa; Cannell, Elisabeth; Hardowar, Khemraj; Hanley, Kathleen; Gillespie, Colleen; Zabar, Sondra
Abstract : Objective structured clinical examinations (OSCEs) provide a controlled, simulated setting for competency assessments, while unannounced simulated patients (USPs) measure competency in situ or real-world settings. This exploratory study describes differences in primary care residents' skills when caring for the same simulated patient case in OSCEs versus in a USP encounter. Data reported describe a group of residents (n=20) who were assessed following interaction with the same simulated patient case in two distinct settings: an OSCE and a USP visit at our safety-net clinic from 2009 to 2010. In both scenarios, the simulated patient presented as an asthmatic woman with limited understanding of illness management. Residents were rated through a behaviourally anchored checklist on visit completion. Summary scores (mean % well done) were calculated by domain and compared using paired sample t-tests. Residents performed significantly better with USPs on 7 of 10 items and in two of three aggregate assessment domains (p<0.05). OSCE structure may impede assessment of activation and treatment planning skills, which are better assessed in real-world settings. This exploration of outcomes from our two assessments using the same clinical case lays a foundation for future research on variation in situated performance. Using both assessments during residency will provide a more thorough understanding of learner competency.